A numerical study of the influence of pilot fuel injection timing on combustion and emission formation under two-stroke dual-fuel marine engine-like conditions. (15th March 2022) - Nemati, Arash; Ong, Jiun Cai; Pang, Kar Mun; Mayer, Stefan; Walther, Jens Honoré
Abstract: Stricter regulations imposed on emissions are motivating the scientific community to consider studying alternative fuels to achieve low emission, high efficient dual-fuel (DF) marine engines. In this context, three dimensional computational fluid dynamic (CFD) simulations are performed to study the combustion and emission formation under two-stroke, dual-fuel marine engine-like conditions. The DF engine configuration consists of a pilot diesel fuel and a high-pressure, direct injection (HPDI) of natural gas (NG). The simulation results are validated under both high load (high charge density) and low load (low charge density) operating conditions. Detailed analysis of the flame development and emission formation are performed. The interaction between the pilot diesel jets and the methane flame jets is studied. Based on the results, the further methane jets penetration in the low load case leads to better air–fuel mixing and a higher combustion intensity than that in the high load. Effects of the pilot fuel injection timing on combustion and emission formation and the governing mechanisms are also investigated in detail. Results indicate that the intense combustion of the accumulated methane expands the methane flame towards the piston when the pilot injection timing is retarded. The NO formation is lower in the high load case with higher charge density due to the lower combustion intensity. Also, retarding the pilot injection timing decreases the NO formation. Highlights: Study the development of diesel and methane flames in pilot-ignited dual-fuel engine. Low charge density condition shows a higher combustion rate than high density. Retarding the pilot injection timing expands the methane flame towards the piston. Retarding the pilot injection timing and increasing charge density reduce NO emission.